2014
DOI: 10.1080/0267257x.2014.971045
|View full text |Cite
|
Sign up to set email alerts
|

An environmental social marketing intervention among employees: assessing attitude and behaviour change

Abstract: Additional information:Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 113 publications
2
38
0
1
Order By: Relevance
“…; Gregory‐Smith et al . ) have shown encouraging results. Furthermore, social marketing has been recommended as a means to reduce demand for wildlife (Drury ; Challender & MacMillan ), but there is little information on its effectiveness in reducing demand or supply (but see Saypanya et al .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…; Gregory‐Smith et al . ) have shown encouraging results. Furthermore, social marketing has been recommended as a means to reduce demand for wildlife (Drury ; Challender & MacMillan ), but there is little information on its effectiveness in reducing demand or supply (but see Saypanya et al .…”
Section: Introductionmentioning
confidence: 91%
“…Social marketing uses marketing techniques to change behavior, including identifying barriers and benefits to the promoted behavior and tailoring efforts to change behavior to segments of target audiences (Andreasen 1994;McKenzie-Mohr 2011). Studies on the effectiveness of social marketing within conservation and environmental applications, such as management of fish, forests, water, and energy (Andriamalala et al 2013;Cole & Fieselman 2013;Martinez et al 2013;Gregory-Smith et al 2015) have shown encouraging results. Furthermore, social marketing has been recommended as a means to reduce demand for wildlife (Drury 2011;Challender & MacMillan 2014), but there is little information on its effectiveness in reducing demand or supply (but see Saypanya et al 2013;Liu et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The environmental agenda will continue to have an important effect on marketing theory and practice (Kotler, 2011). Environmental social marketing campaigns have been launched as attempts to effect change in energy conservation (Gray & Bean, 2011), litter reduction (Almosa, Parkinson & Rundle-Thiele, 2017), recycling at the office (Gregory-Smith, Wells, Manika & Graham, 2015), plastic bag use (Carrigan, Moraes & Leek, 2011) and water consumption (Lowe, Lynch & Lowe, 2014), among others. In most of the cases listed above, the desired outcome would be behavioural changes across multiple target markets and customer segments.…”
Section: Social Marketing Environmental Campaigns and Nascent Soil mentioning
confidence: 99%
“…Abrahamse et al, 2005;Steg and Vlek, 2009), more recently, research aims to understand and promote pro-environmental behaviour at work (e.g. Gregory-Smith et al, 2015). In addition to the home, the workplace is one of the main 'microenvironments' where people spend most of their day-to-day time (Cox et al, 2012), which is why the workplace is an important setting for promoting sustainable lifestyles.…”
Section: Spillover In the Workplacementioning
confidence: 99%